(untitled) (Global Journal of Computer Science and Technology, 2023)
This article suggests a cognitive approach to initiate the inclusion of unperceivable worlds into established ontologies We qualify as unperceivable any world that escapes automatic data exploration because of the leak of sufficient documentation Initially based on knowledge engineering the approach aims in the long term at the automatic production of knowledge vectors that can be assimilated to existing corpora It leverages a proven and extendable universal ontology and is experienced in the emerging world of Malagasy culture